Օտար լեզվի ուսուցման հետ կապված հոգեբանական դժվարություններն ու խնդիրները. Ամենից շատ հանդիպող լեզվա-քերականական սխալները և նրանց հաղթահարման ուղիներն անգլերենում - Հասմիկ Աբրահամյան (ՀՀ ԳԱԱ հրատ.)
В данной статье обсуждаются те психологические проблемы, которые мешают учащимся общаться на английском. Рекомендуются способы преодоления данных психологических и языковых барьеров и проблем. На конкретных примерах раскрываются некоторые общие лингво-грамматические ошибки, с которыми учащиеся сталкиваются наиболее часто. Особое внимание уделяется развитию языкового мышления. The given article discusses the psychological problems that prevent students to communicate in English. Ways are recommended to overcome these psychological and language barriers and problems. Some common linguistic and grammatical errors are revealed on specific examples that students encounter most often. Particular attention is paid to the development of linguistic thinking.
Keywords: Psychology; Education; Theory and practice of education